Conditioning the neuroimmune response to ethanol using taste and environmental cues in adolescent and adult rats. Issue 5 (April 2019) - Gano, Anny; Pautassi, Ricardo M; Doremus-Fitzwater, Tamara L; Barney, Thaddeus M; Vore, Andrew S; Deak, Terrence
Our work in adult Sprague-Dawley rats has shown elevation of the cytokine Interleukin (IL)-6 in the hippocampus and amygdala following acute and repeated binge-like doses of ethanol during intoxication. Previously, we have shown that in adults, the central IL-6 response to a sub-threshold dose of ethanol was sensitized by repeated pairings of ethanol as an unconditioned stimulus (US) with an odor conditioned stimulus (CS).In the present studies, acute ethanol exposure (4 g/kg intraperitoneal) was paired with a combined odor and taste cue using a single trial learning procedure, after which rats were tested for conditioned effects of the CS on neuroimmune gene expression. We found that IL-6 was significantly elevated in the amygdala based on exposure to the CS after just one CS–US pairing in young adolescent rats (age P32–40), an effect that was more modest in young adults (P72–80). These data indicate that, despite a normal disposition toward a blunted neuroimmune response to ethanol, adolescents were more sensitive than adults to forming learned associations between ethanol's neuroimmune effects and conditioned stimuli. Given the emergent role of the immune system in alcoholism, such as regulating ethanol intake, these ethanol-induced conditioned effects on cytokine levels may contribute to our understanding of the unique attributes that make adolescence a time period of vulnerability in the development of later alcohol abuse behaviors. Impact statement: A combined odor and taste cue was paired with a binge-like ethanol exposure (4 g/kg intraperitoneal) using a single-trial learning paradigm. Re-exposure to the CS alone was sufficient to evoke a conditioned Interleukin (IL)-6 elevation in the amygdala in adolescents, an effect that was not observed in young adults. This demonstrates a particular sensitivity of adolescents to alcohol-associated cues and neuroimmune learning, whereas prior work indicated that adults require multiple pairings of ethanol to the CS in order to achieve a conditioned amygdala IL-6 response. While the role of immune conditioning has been studied in other drugs of abuse, these findings highlight a previously unknown aspect of alcohol-related learning. Given the emergent importance of the neuroimmune system in alcohol abuse, these findings may be important for understanding cue-induced reinstatement of alcohol intake among problem drinkers.